Single nucleotide polymorphism in Osteopontin gene and its association with milk traits in Azikheli buffalo - Arshia Rauf; Sohail Ahmad; Sundus Altaf; Shehryar Khattak; Bibi Sabiha; Muhammad Ibrahim (Acta Scientiarum: Animal Sciences)
Osteopontin (OPN) is known to effect milk composition traits. This study aimed to associate OPN gene polymorphism with milk traits in Azikheli buffaloes. Data were collected for milk yield and milk composition from 30 buffaloes. DNA samples of these specimen were used to amplify exon 4, intron 4 and exon 6 of the OPN gene using predesigned primers. The PCR products were sequenced through Sanger sequencing. The results showed that the milk yield varied significantly (p < 0.001) among Azikheli buffaloes. Sanger sequencing revealed 24 SNPs in the targeted regions of OPN, among which 2 were found in the high yielding buffaloes, while 23 were in the low yielding buffaloes of which one SNP was shared. One novel SNP g.5096T>C in the intron 5 of the OPN gene showed significant association with milk yield and milk protein. non-synonymous substitutions were observed at different loci i.e., g.5521C>T (Asp108Glu), g.5505C>T (Ala128Val), g.5446T>A (Thr149Ala), and 5395CGA>DEL (Asp92Del). Among the non-synonymous mutations only Ala128Val was found to have effect on protein stability (DDG = – 0.92 kcal mol-1) due to its presence in the conserved region of the protein. In conclusion, our results suggest SNP g.5096T>C as a potential genetic marker for high milk yield in Azikheli buffalo.